2002
DOI: 10.1111/j.1945-1474.2002.tb00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Patient Satisfaction in a Military Teaching Hospital

Abstract: The purpose of this study was to determine the aspects of hospital services that are most likely to affect patient satisfaction in a military teaching hospital in Turkey. Although there have been many studies on patient satisfaction in Turkey and other countries, few studies have been done in military hospitals. A patient satisfaction questionnaire using a 4-point Likert scale was mailed to 500 patients after discharge, and 316 questionnaires were returned. The findings indicated that satisfaction with physici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 17 publications
3
25
1
Order By: Relevance
“…Additionally, as recommended by Gok and Sezen (2013), small and medium sized hospitals may consider larger hospitals as a role model in terms of quality of health care. Similarly, in accordance with earlier findings (Demir & Celik, 2002;Thi, 2002;Laal, 2013), the results of this study found that married patients were more likely to be very satisfied.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Additionally, as recommended by Gok and Sezen (2013), small and medium sized hospitals may consider larger hospitals as a role model in terms of quality of health care. Similarly, in accordance with earlier findings (Demir & Celik, 2002;Thi, 2002;Laal, 2013), the results of this study found that married patients were more likely to be very satisfied.…”
Section: Discussionsupporting
confidence: 82%
“…Meanwhile, waiting time for health care was significant in the literature (Boudreaux et al, 2000;Brown et al, 2005;French et al, 2014;Mercer et al, 2014). Some past studies (Demir & Celik, 2002;Jenkinson et al, 2002;Scotti & Stinerock, 2002;Merkouris et al, 2004;Baalbake et al, 2008;Kim et al, 2008;Miranda et al, 2010;Johannessen et al, 2011;Otani et al, 2012;Tateke et al, 2012;Chang & Chang, 2013;Gok & Sezen, 2013) found that hospital facilities were significant contributing factors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations